A history of advertising - Pincas, Stéphane, ....-; Loiseau, Marc, ....- (Cologne : Taschen, 2008)
The history of western advertising dates back at least the 1630s, when Frenchman Théophraste Renaudot placed the first advertising notes in La Gazette de France. In 1786, William Tayler offered his services as "Agent to the Country's Printers, Booksellers, etc," but the term "advertising agency" originated in 1842, when Volney B. Palmer opened for business in Philadelphia. Widely accepted as the birth of modern advertising, this marks the beginning of a creative industry that has radically transformed our culture and language. Divided into sections by decades, this book explores the legendary campaigns and brands of advertising's modern history, with specific anecdotes and comments on the importance of every campaign. You will find the picture of the camel that originated the Camel pack, the first Coca Cola ad, and even how artworks by masters such as Picasso and Magritte have been used in advertising.
Keywords: Adverteren; Reclame